Gildardo Magaña and his Intellectual Work in favor of Zapatismo: his Facet as an Ideologue and Historian - Luis Sánchez Amaro (Латиноамериканский исторический альманах, 2022)
This paper analyzes the biographical profile of Gildardo Magaña and the reasons why he adheres to the revolutionary movement led by Emiliano Zapata in the state of Morelos, to immediately explain what his work as an ideologue and historian of the Zapatista movement consisted of; a task that began years after the death of the leader of the south and with which he sought to claim the importance of this current in the revolu-tionary process that began in 1910 and in favor of the peasant struggle. Task in which he highlighted his determination to achieve the historical claim of thought, the military, political and social action of its main leader Emiliano Zapata, who was unjustly reviled in life and after his tragic death, in April 1919, by his enemies.